THE PSYCHOLOGIST IN FRONT OF THE PATIENT IN THE TERMINAL SITUATION - Barreto Martín, María Pilar; Bayés, Ramón (Anales de Psicología / Annals of Psychology)
Many old people are victims of incurable illnesses who suffer greatly in the weeks preceeding death. Palliative care is an alternative approach that is really useful for terminal patients. The main aim in palliative care is to ensure the patient’s comfort or wellbeing. Psychologists, working in a health interdisciplinary team, are a very important key in this task, both, in research and clinical practice.